Analisis Jenjang Metakognisi Berdasarkan Jenis Kelamin Siswa SMA Negeri 1 Dampal Selatan Memecahkan Masalah Termokimia - Hariani Hariani; Ijirana Ijirana; Suherman Suherman; Meida Esterlina Marpaung (JURNAL BANUA OGE TADULAKO, 2022)
In the process of studying chemistry there is a demand for the development of scientific thinking skills. In the process of developing scientific thinking skills, this means that there is a process of growing problem-solving skills. Problem-solving abilities are closely related to metacognition. This study aims to analyze and describe the relationship between the level of metacognition and gender of students. This research was conducted at SMA Negeri 1 Dampal Selatan with 90 students as research subjects. This research is a qualitative descriptive study so that the data is in the form of essay test results. The results of the essay test were grouped by gender, then analyzed and determined by the level of metacognition based on indicators of metacognition level. The results obtained from this study are female students are more active and have a higher level of metacognition than male students.